Structure mediation in substrate binding and post-translational processing of penicillin acylases: Information from mutant structures of Kluyvera citrophila penicillin G acylase - Chand, Deepak; Varshney, NishantKumar; Ramasamy, Sureshkumar; Panigrahi, Priyabrata; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Protein Science, 2015)
Penicillin acylases are industrially important enzymes for the production of 6-APA, which is used extensively in the synthesis of secondary antibiotics. The enzyme translates into an inactive single chain precursor that subsequently gets processed by the removal of a spacer peptide connecting the chains of the mature active heterodimer. We have cloned the penicillin G acylase from Kluyvera citrophila (KcPGA) and prepared two mutants by site-directed mutagenesis. Replacement of N-terminal serine of the beta-subunit with cysteine (Ser beta 1Cys) resulted in a fully processed but inactive enzyme. The second mutant in which this serine is replaced by glycine (Ser beta 1Gly) remained in the unprocessed and inactive form. The crystals of both mutants belonged to space group P1 with four molecules in the asymmetric unit. The three-dimensional structures of these mutants were refined at resolutions 2.8 and 2.5 angstrom, respectively. Comparison of these structures with similar structures of Escherichia coli PGA (EcPGA) revealed various conformational changes that lead to autocatalytic processing and consequent removal of the spacer peptide. The large displacements of residues such as Arg168 and Arg477 toward the N-terminal cleavage site of the spacer peptide or the conformational changes of Arg145 and Phe146 near the active site in these structures suggested probable steps in the processing dynamics. A comparison between the structures of the processed Serb1Cys mutant and that of the processed form of EcPGA showed conformational differences in residues Arg alpha 145, Phe alpha 146, and Phe beta 24 at the substrate binding pocket. Three conformational transitions of Arg alpha 145 and Phe alpha 146 residues were seen when processed and unprocessed forms of KcPGA were compared with the substrate bound structure of EcPGA. Structure mediation in activity difference between KcPGA and EcPGA toward acyl homoserine lactone (AHL) is elucidated.
Keywords: acyl homoserine lactone; autocatalytic processing; conformational changes; KcPGA_Ser beta 1Cys; KcPGA_Ser beta 1Gly; Ntn hydrolase